(3TQhW GJaGb GdJMcje hGKGQg (B/ s - (3HGSeI dWai OHGSs; (3GMeO GdSjO UGhi (B: s; (3LGeYI GdbGgQI s ((3GdbGgQI (B: s (3cdjIGdMbhb (B- (3LGeYI GdbGgQI , s, 2005)
(3cGf ef TGf RjGOI eYOd GdJLGQI GdOhdjI hfehgG hJWhQ GdYdGbGJ GdJLGQjI Hjf GdTQb hGdZQH Gf GUHMJ MbjbI KGHJI JNWJ YHQ GdMOhO hcGf ef TGfgG GaQGR GfhGY LOjOI ef GdeYGedGJ hGdYbhO GdJi de jcf ddacQ GdbGfhfi SGHb YgO HgG agi eYGedGJ hYbhO eQcHI hWhjdI GdeOIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeQGaYGJ (B2005s
(3HHdjhLQGajGJ (B558 - 600s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3bGfhf GdeQGaYGJs; (3GJaGb GdJMcjes; (3GdJLGQI GdOhdjIs; (3GdacQ GdbGfhfis; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQI s -- (3cdjI GdMbhbs